Shock Wave Study of the Thermal Dissociations of C3F6 and c-C3F6. I. Dissociation of Hexafluoropropene - Cobos, Carlos Jorge (2014)
The thermal dissociation of C3F6 was studied between 1330 and 2210 K in shock waves monitoring the UV absorption of CF2. CF2 yields of about 2.6 per parent C3F6 were obtained at reactant concentrations of 500-1000 ppm in the bath gas Ar. These yields dropped to about 1.8 when reactant concentrations were lowered to 60 ppm. The increase of the CF2 yield with increasing concentration was attributed to bimolecular reactions between primary and secondary dissociation products. Quantum-chemical and kinetic modeling calculations helped to estimate the contributions from the various primary dissociation steps. It was shown that the measurements correspond to unimolecular reactions in their falloff range. Falloff representations of the rate constants are given, leading to an overall high pressure rate constant k∞ = 2.0 × 10(17)(-104 kcal mol(-1)/RT) s(-1) and a relative rate of about 2/3:1/3 for the reactions C3F6 → CF3CF + CF2 versus C3F6 → C2F3 + CF3.